2004
DOI: 10.1242/jeb.00741
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial response of gastric pH in leopard sharks (Triakis semifasciata)and its use to study foraging ecology

Abstract: Changes in gastric pH of leopard sharks Triakis semifasciata were quantified as an indicator of feeding frequency and ration size. Continuous in situ measurements of gastric pH were made in captive adult leopard sharks using an autonomous pH/temperature probe for periods ranging from 5-16 days. Instrumented sharks were fed meals of squid at different ration sizes. Gastric fluid samples were also taken from noninstrumented juvenile leopard sharks at different time intervals after feeding, and the pH measured to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…It is also possible that these fish had died and were scavenged by a predator (e.g., sealion Zalophus californianus or shark) and the predator was detected moving between these platforms. However, a predator that has consumed a transmittered fish should regurgitate the transmitter after 5-10 d (Papastamatiou and Lowe 2004).…”
Section: Groundfish Site Fidelity and Movement Patternsmentioning
confidence: 99%
“…It is also possible that these fish had died and were scavenged by a predator (e.g., sealion Zalophus californianus or shark) and the predator was detected moving between these platforms. However, a predator that has consumed a transmittered fish should regurgitate the transmitter after 5-10 d (Papastamatiou and Lowe 2004).…”
Section: Groundfish Site Fidelity and Movement Patternsmentioning
confidence: 99%
“…In marine ecosystems, the advent of electronic tags has provided unprecedented new insights into movements of highly mobile sharks and fishes (Meyer et al, 2007;Meyer et al, 2010), but we still know very little about where and when these animals are feeding or how much they are eating (Papastamatiou and Lowe, 2004;Bestley et al, 2008). We need this information both to understand the ecology of individual species and to gain a broader understanding of patterns of energy flow through marine food webs.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the utility of stomach temperature telemetry alone for quantifying feeding in fishes and sharks appears to be limited to a small number of endothermic species that either utilize visceral warming to aid digestion (Bestley et al, 2008) or maintain relatively warm stomach temperatures and ingest cool prey (and cool seawater) during feeding (Goldman, 1997;Papastamatiou and Lowe, 2004). However, even in endothermic fishes, interpretation of cold spikes in stomach thermal records could be confounded by fishes drinking cool seawater (Wood et A more broadly applicable and unequivocal measure of feeding is clearly needed and in recent years stomach pH tags were successfully used to identify feeding events and quantify meal size in captive poikilothermic sharks (Papastamatiou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and the other is characterized by continuous acid secretion and the maintenance of a low, acidic pH during fasting (Papastamatiou and Lowe, 2004;Bucking and Wood, 2009). Our results demonstrated that C. argus and S. chuatsi hold a closely neutral pH in the stomach mucosa through a long period of fasting, acidification perhaps only stimulated by the ingestion of food (Nikolopoulou et al, 2011).…”
mentioning
confidence: 99%